Investigating Thermal Effect on a Cross Linked Polyethylene Power Cable - Emna Khouildi; Rabah Attia; Rafik Cherni (Institute of Advanced Engineering and Science, 2017)
One of the agents responsible of the degradation of power cables in electrical distribution network is the temperature. In this paper, numerical modelling of temperature effect on the cross linked polyethylene (XLPE) insulation of a medium voltage cable containing internal defects, which are air void cavity and water tree cavities, is developed by using the finite element method and simulated by COMSOL Multiphysics Software. The experimental investigation is conducted through studying parial discharge inception voltages in XLPE insulation before and after 23 heating cycles of a 7 meters sample of a medium voltage cable at 100°C and 120°C temperatures. Partial discharge inception voltages detection were performed using the IEC60270 test method. The simulation results and experimental measurements assessed the thermal effect on the degradation of XLPE insulation.